Flow structures and thermal field with modulated jet near the semi-circular leading edge. (August 2020) - Sarkar, S
Influence of external modulation on unsteady flow and heat transfer near the leading edge of a constant thickness aerofoil has been described through large eddy simulation. This is a simplified approach to study film cooling activities near the leading edge of a turbine blade. Discrete jets, which are forced at a Strouhal number (St) of 0.37 with an averaged blowing ratio of unity, are ejected normally from a series of film cooling holes to a separated boundary layer. The results are compared against the corresponding steady injection. Larger coherent structures appear for a forced jet with an augmented vortex dynamics resulting in high jet lift-off, earlier break down, enhanced mixing with the cross flow and dilution of coolant layer. Resolved hairpins, which are the signature of coherent structures, illustrate that the vorticity and thermal field are highly correlated. Furthermore, evolution of hairpins and their advection control scalar transport and mixing. In brief, the modulation of coolant jet near the leading edge appears not beneficial for the combination of blowing ratio and frequency considered here.